The Devil Is in the Details: Linking Home Buyout Policy, Practice, and Experience After Hurricane Sandy - Binder, Sherri Brokopp (2016)
Federal housing recovery policy bounds many of the decisions made by households after a disaster. Within this policy domain, home buyout programs are increasingly used to encourage residents to permanently relocate out of areas considered at risk for future hazards. While buyouts offer homeowners and governments potential benefits, research exploring the impacts of these policies is limited. In this paper, we present an in-depth examination of the community experience of buyouts, a perspective that is noticeably lacking in the literature. Using data from two mixed-method empirical studies, we explored the implications of buyout program design and implementation for Oakwood Beach, New York, a community offered a buyout after Hurricane Sandy. We found that  design decisions made at program conception significantly impacted participants’ experience of the buyout, including their understanding of program goals and their progression through the buyout and relocation process. We conclude with recommendations for future buyouts, including increased inclusion of affected communities in the process of and pre-event planning for recovery, along with recommendations for future research.